Turismo e patrimônio cultural: processo de tombamento e estratégias de utilização turística do Centro Histórico de Natal/RN - Melo, Maria Augusta Wanderley Seabra de (2015)
In a globalized society, the relations between heritage and tourism are reflected in an ambiguous reality, shaped between the interests of preservation and the aspirations for economic benefits. On the one hand, the cities as a main generating cultural offerings needs to contemplate its heritage as a development axis, finding in the cultural tourism promotion a strategy to support the high cost of recovery and maintenance of its historical center and its expressions cultural. On the other, adds to the new requirements of demand, causing the tourism projects to turn to the cultural factor in the formation of their products, which allows municipalities to attract the growing cultural tourism segment. In this perspective, this study develops into a focused cross-cut in the analysis of Natal’s Historical City Center, in order to understand how this cultural heritage fallen has been used by the municipal administration for tourism. By understanding the heritage as a reference to identity and memory, as well as a cultural symbol of Natal society, characterized as an element surrounded by complex and strictly private situations, it identified the need for a qualitative approach to his deep understanding. The in-depth case study developed in two stages, first the realization of bibliographical and documentary research; and thereafter the interpretation of data collected through semi-structured interviews with municipal administrators and local residents. The survey results show that the official representatives of heritage are concerned about the preservation of the material dimension of the architectural heritage of the city, however, still can not reach and sensitize the local population, which seems to be part of a process that should be democratic and strengthening the sense of belonging of these people. Finally, it indicates an absence of revitalization strategies by the current municipal public administration for Natal’s Historical City Center, revealing a speech covered by a positivist interpretation of tourism, which deals with the use of assets by the scope of the marketing empiricism.